Quantitative and Qualitative Differences in the In Vivo Response of NKT Cells to Distinct α- and β-Anomeric Glycolipids - Parekh, V; Singh, A; Wilson, M; Olivares-Villagómez, D; Bezbradica, J; Inazawa, H; Ehara, H; Sakai, T; Serizawa, I; Wu, L; Wang, C; Joyce, S; et al. (American Association of Immunologists, 2004)
NKT cells represent a unique subset of immunoregulatory T cells that recognize glycolipid Ags presented by the MHC class I-like molecule CD1d. Because of their immunoregulatory properties, NKT cells are attractive targets for the development of immunotherapies. The prototypical NKT cell ligand alpha-galactosylceramide (alpha-GalCer), originally isolated from a marine sponge, has potent immunomodulatory activities in mice, demonstrating therapeutic efficacy against metastatic tumors, infections, and autoimmune diseases, but also has a number of adverse side effects. In vivo administration of alpha-GalCer to mice results in the rapid activation of NKT cells, which is characterized by cytokine secretion, surface receptor down-regulation, expansion, and secondary activation of a variety of innate and adaptive immune system cells. In this study, we have evaluated the in vivo immune response of mice to a set of structural analogues of alpha-GalCer. Our results show that, contrary to current thinking, beta-anomeric GalCer can induce CD1d-dependent biological activities in mice, albeit at lower potency than alpha-anomeric GalCer. In addition, we show that the response of NKT cells to distinct GalCer differs not only quantitatively, but also qualitatively. These findings indicate that NKT cells can fine-tune their immune responses to distinct glycolipid Ags in vivo, a property that may be exploited for the development of effective and safe NKT cell-based immunotherapies.